Acute Leukemia Induces Senescence and Impaired Osteogenic Differentiation in Mesenchymal Stem Cells Endowing Leukemic Cells with Functional Advantages - Ximena Bonilla; Natalia-Del Pilar Vanegas; Jean Paul Vernot (Stem Cells International)
Mesenchymal stem cells (MSC) constitute an important cell population of the bone marrow hematopoietic niche that supports normally hematopoietic stem cells (HSC) but eventually also leukemic cells. The alterations that occur in the MSC under leukemic stress are not well known. To deepen on this topic, we have used an in vitro model of the leukemic niche (LN) by coculturing MSC with an acute lymphocytic leukemia cell line (REH) and proceeded to evaluate MSC characteristics and functions. We found that leukemic cells induced in MSC a significant increase both in senescence-associated β-galactosidase activity and in p53 gene expression. MSC in the LN also showed a persistent production of cytoplasmic reactive oxygen species (ROS) and a G2/M phase arrest of the cell cycle. Another acute leukemic cell line (SUP-B15) produced almost the same effects on MSC. REH cells adhere strongly to MSC possibly as a result of an increased expression of the adhesion molecules VCAM-1, ICAM-1, and CD49e in MSC and of CD49d in REH cells. Although mesensphere formation was normal or even increased, multipotent differentiation capacity was impaired in MSC from the LN. A REH-conditioned medium was only partially (about 50%) capable of inducing the same changes in MSC, suggesting that cell-to-cell contact is more efficient in inducing these changes. Despite these important effects on MSC in the LN, REH cells increased their cell adhesion, proliferation rate, and directed-migration capacity. In conclusion, in this in vitro LN model, leukemic cells affect importantly the MSC, inducing a senescence process that seems to favour leukemic cell growth.